Efficacy of XP-Endo Finisher in the Removal of Triple Antibiotic Paste from Immature Root Canals - TÜRKAYDIN, DİLEK; BAŞTÜRK, FATIMA BETÜL; SAZAK ÖVEÇOĞLU, HESNA (ELSEVIER SCIENCE INC, 2017)
Introduction: The aim of this study was to evaluate and compare the effectiveness of the XP-Endo Finisher (FKG Dentaire, La Chaux-de-Fonds, Switzerland) with passive ultrasonic irrigation (PUI) and needle irrigation in the removal of triple antibiotic paste (TAP) from the straight immature root canals of extracted teeth. Methods: Thirty-four freshly extracted single-rooted teeth were used. All canals were prepared up to the ProTaper F5 file (Dentsply Maillefer, Ballaigues, Switzerland). Apices were drilled to simulate teeth with immature apices. The canals were filled with TAP, sealed, and incubated at 37 degrees C and 100% humidity for 1 month. Samples were randomly assigned to 3 experimental groups according to the method used for TAP removal: XP-Endo Finisher, PUI, and needle irrigation (n = 10). Then, the roots were split into 2 halves. The amount of TAP residue in the apical portion of each segment was evaluated using a scanning electron microscopy and scored. Results: The amount of remaining TAP was significantly lower in the XP-Endo Finisher group compared with the needle irrigation and PUI groups (P < .05). Between the needle irrigation and PUI groups, there were no statistically significant differences (P> .05). Conclusions: Within the limitations of this study, the XP-Endo Finisher removed significantly more TAP than needle irrigation and PUI.
Keywords: Passive ultrasonic irrigation; scanning electron microscopy; triple antibiotic paste; XP-Endo Finisher; CALCIUM HYDROXIDE; IN-VITRO; ENDODONTIC REGENERATION; INTRACANAL MEDICAMENTS; APICAL PERIODONTITIS; RADICULAR DENTIN; STEM-CELLS; IRRIGATION; TEETH; REVASCULARIZATION